Improving solar radiation source efficiency using adaptive dynamic squirrel search optimization algorithm and long short-term memory - Khafaga, Doaa Sami; Alhussan, Amel Ali; Eid, Marwa M.; El-kenawy, El-Sayed M. (Frontiers in Energy Research, 2023)
Artificial intelligence and machine learning are used to optimize the design parameters of renewable energy sources, which are now regarded as vital components in current clean energy sources. As a result, system requirements can be reduced, and a well-designed system can improve performance. Artificial intelligence approaches in renewable energy sources and system design would significantly cut optimization time while maintaining high modeling accuracy and optimum performance. This study examines machine learning in-depth, emphasizing how it can be used in developing renewable energy sources because of the vast range of technologies it can use. This paper approximates the hourly tilted solar irradiation using climate factors. The irradiance is estimated using a hybrid ensemble-learning approach. This approach combines a proposed Adaptive Dynamic Squirrel Search Optimization Algorithm (ADSSOA) with Long Short-Term Memory (LSTM) methods. To the best of our knowledge, this combination has not been used for solar radiation. The results are analyzed and contrasted with the outcomes of several recent swarm intelligence algorithms, such as the Genetic Algorithm (GA), Particle Swarm Optimization (PSO), and Grey Wolf Optimizer (GWO). The binary Adaptive Dynamic Squirrel Search Optimization approach performed as expected, with an average error of 0.1801 and a standard deviation of 0.0656. The ADSSOA-LSTM model had the lowest RMSE (0.000388) compared to LSTM's (0.001221). In addition, the statistical analysis uses ten iterations of each presented and evaluated method to provide accurate comparisons and reliable results.